DAMPAK PODCAST SEBAGAI MEDIA KOMUNIKASI BARU TERHADAP GAYA BELAJAR MAHASISWA INSTITUT TEKNOLOGI DAN BISNIS TRENGGALEK - Prasetyaningrum, Ria (STAI Nurul Falah Airmolek, 2024)
information and introducing new ways of learning. Its presence has brought new flexibility to education, allowing students to study while doing other activities. However, the impact on student learning styles still needs to be understood more deeply, especially in academic environments such as the Trenggalek Institute of Technology and Business. Student learning styles, which are individual preferences for processing information, can be influenced by the use of technology such as podcasts. Therefore, this research aims to investigate how the use of podcasts influences the learning styles of students at Trenggalek Institute of Technology and Business. The literature review shows that podcasts, as an audiovisual medium, can cater to a variety of learning styles. However, student responses to the use of podcasts in learning contexts still need further research. This research uses a descriptive qualitative approach and literature review methods to collect and analyze data. Results show that podcasts provide flexibility in time and place, access to diverse resources, and support auditory learning styles. However, some negative aspects such as lack of visual support and potential distractions also need to be considered